2008
DOI: 10.2527/jas.2007-0206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dried corn distillers grains plus solubles compared with soybean hulls, in late gestation heifer diets, on animal and reproductive performance1

Abstract: Dried distillers grains plus solubles (DDGS) contain fat and rumen undegradable intake protein, both of which have been shown to increase reproductive performance in heifers. The mechanisms leading to enhanced reproduction have not been fully defined. The objectives of this research were to evaluate effects of DDGS in late gestation heifer diets on animal and reproductive performance and on blood plasma concentrations of GH, IGF-I, and NEFA. Over 2 yr, 201 heifers were randomly allotted to 1 of 2 diets, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 43 publications
0
39
0
3
Order By: Relevance
“…Also, fat concentrations were elevated in the DDGS diets in the present experiment and a greater percentage of UFAs in DDGS have been reported to bypass ruminal biohydrogenation compared with control diets (Vander Pol et al, 2009). It has been proposed that fat supplementation, specifically PUFAs (Mattos et al, 2000), or a combination of both fat and CP (Engel et al, 2008;Gunn et al, 2014) improve reproductive performance. The specific nutrient and the mechanism by which fat, PUFAs, protein, or their combination increase TAI conception rates remains to be elucidated.…”
Section: Shee Lemenager and Schoonmakermentioning
confidence: 45%
See 2 more Smart Citations
“…Also, fat concentrations were elevated in the DDGS diets in the present experiment and a greater percentage of UFAs in DDGS have been reported to bypass ruminal biohydrogenation compared with control diets (Vander Pol et al, 2009). It has been proposed that fat supplementation, specifically PUFAs (Mattos et al, 2000), or a combination of both fat and CP (Engel et al, 2008;Gunn et al, 2014) improve reproductive performance. The specific nutrient and the mechanism by which fat, PUFAs, protein, or their combination increase TAI conception rates remains to be elucidated.…”
Section: Shee Lemenager and Schoonmakermentioning
confidence: 45%
“…Studies with heifers have reported a decrease in postpartum anestrous when feeding 40% to 50% DDGS during late gestation (Engel et al, 2008) or when feeding 43% DDGS during late gestation and early lactation (Gunn et al, 2014). Pregnancy rates have improved for some studies when DDGS was fed during late gestation (Engel et al, 2008), but TAI and overall pregnancy rates have not been altered in other studies when DDGS was fed during late gestation (Radunz et al, 2010) or during early lactation (Shike et al, 2009). Gunn et al (2014) observed that DDGS increased follicle growth rates, increased dominant follicle diameters and decreased the anestrous period compared with control fed cows.…”
Section: Shee Lemenager and Schoonmakermentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were placed at 4 • C for approximately 24 h. Samples were centrifuged at 1200 × g for 25 min at 4 • C and serum was collected and stored at −20 • C until radioimmunoassays were performed. Radioimmunoassay (RIA) was performed on serum samples to measure progesterone concentrations using the methods described by Engel et al (2008). Inter-and intra-assay CV were 13.67% and 4.52%, respectively and assay sensitivity was 0.4 ng/mL.…”
Section: Blood Collection and Riamentioning
confidence: 99%
“…Plasma was frozen and all samples were subsequently analyzed for concentrations of P4 by radioimmunoassay as described [18]. Intra-and interassay coefficients of variation for P4 assays were 2.3% and 6.4%, respectively, and assay sensitivity was 0.4 ng/mL.…”
Section: Radioimmunoassays For E2 and P4mentioning
confidence: 99%